SCIENTIFIC AND THEORETICAL BASIS FOR FINANCING HIGHER EDUCATION INSTITUTIONS (American Journal of Business Management, Economics and Banking, 2026)
This article attempts to analyze the economic content, functions, and principles of financing higher education institutions from a scientific and theoretical perspective, as well as to identify the conceptual foundations of financing models. The results of this study serve to improve financial policy in higher education and effectively organize investments in human capital.